2017
DOI: 10.3892/mmr.2017.7333
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of mesenchymal stem cells from human amniotic fluid to cardiomyocyte-like cells

Abstract: Ischemic heart disease (IHD) is a major factor influencing worldwide mortality rates. Furthermore, IHD has become a significant health problem among the Thai population. Stem cell therapy using mesenchymal stem cells (MSCs) is an alternative therapeutic method that has been applied to improve the quality of life of patients. Amniotic fluid (AF) contains a heterogeneous cell population, including MSCs, which are multipotent stem cells that have the capability to differentiate into mesenchymal lineages. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…The hAF-MSCs obtained from the second-trimester of a pregnancy possess a self-renewal capacity and multilineage differentiation potential [ 18 , 19 , 20 ]. They can differentiate into chondrocytes [ 21 , 22 ], endothelial cells [ 23 ], osteocytes [ 24 ] and cardiomyocytes [ 25 ]. Furthermore, they have been shown to be effective in the treatment of many diseases such as MI [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hAF-MSCs obtained from the second-trimester of a pregnancy possess a self-renewal capacity and multilineage differentiation potential [ 18 , 19 , 20 ]. They can differentiate into chondrocytes [ 21 , 22 ], endothelial cells [ 23 ], osteocytes [ 24 ] and cardiomyocytes [ 25 ]. Furthermore, they have been shown to be effective in the treatment of many diseases such as MI [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus our data collectively suggests that AF-MSC have superior cardiomyogenic potency as compared to BM-MSC. Although, there is no previous report comparing the cardiomyogenic potential of human AF-MSC and BM-MSC, but several studies have also reported a limited cardiomyogenic potential of BM-MSC (6).We have previously shown that BM-MSC exhibit clonal heterogeneity and only 1 out of 4 clones possessed cardiomyogenic potential, highlighting a low frequency of car-diomyogenic cells in BM-MSC (17). It has also been previously shown that AF-MSC have superior neural and hepatic potency in comparison to BM-MSC (13,14).…”
Section: Discussionmentioning
confidence: 84%
“…The potency of hAF-MSCs was confirmed by recent studies that isolated MSCs from the same source. The results showed the differentiation potential of MSCs into chondrocyte, cardiomyocyte and osteoblast [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%